Evaluating the impact of horizontally acquired genes on the metabolism of nonconventional yeast lineage - Gil, Victoria Helena Navas (2023)
The Wickerhamiella/Starmerella (W/S) clade is a group of non-conventional yeast with atypical metabolic functions that enable the colonization of specialized niches, such as flowers or the gut of insects that visit flowers. Comparative genomics demonstrates that one of the main forces that drives metabolic evolution in the W/S clade is the unusual high frequency of horizontally acquired genes, some of which have been deeply studied and characterized. Yet, a high proportion of acquired genes with unknown impact in the W/S-clade metabolism still remains. This work aimed to advance the current understanding of the metabolic evolution in the W/S clade, by analyzing the complete transcriptomes of W. versatilis, W. domercqiae and S. bombicola grown in two different conditions. Comparative transcriptomic analyses between native and acquired genes across the three species were performed in order to provide a first high-throughput evaluation of the impact of the acquired genes on the host metabolism. Quantitative levels of gene expression and patterns of differential expression were studied and analyzed together with functional annotation and the role of acquired genes evaluating e.g. whether it enabled a function normally absent in yeasts. The results indicate that, depending on the species analyzed, the expression levels of acquired genes can either be similar or sig-nificantly lower than native genes. Yet, in all instances, an important proportion of these genes are actively regulated. Expressed acquired genes tend to be fixed by replacing pre-existing genes in the genomes, which were often involved in the assimilation of carbon and nitrogen from minority resources. The whole transcriptome analysis is a tool that perfectly complements current knowledge of whole genome evolution in the W/S clade, especially in understanding the evolutionary impact of horizontal gene transfer events in these yeasts.